Role of head of states at G20 High Level Conference in utilizing environmental of sustainable development on electricity in Indonesia - Rizaldi, Sony; Suhartono, Slamet; Hadi, Syofyan; Michael, Tomy (Technium Social Sciences Journal, 2022)
Dependence on fossil energy sources as fuel for power generation still dominates most systems to meet the needs of electrical energy in Indonesia. Efforts to reduce fossil fuels for power generation and switch to new and renewable energy are pursued by the government with the issuance of regulations concerning the National Energy Policy. The responsibility of the government in the context of national energy management has a very decisive role for the sustainability of the national energy supply that is safe, reliable and environmentally friendly. To implement the provisions of Chapter 11 (2) UURI Number 30 of 2007 concerning Energy. The regulation of the EBT issue is regulated in Chapter 4 (2) and (3) of the Republic of Indonesia Law Number 30/2007, where it is stated that: Chapter 4 (2) New energy resources and renewable energy resources are regulated by the State and utilized for the greatest prosperity of the people. The G20 agreed on the "Bali Compact", which was the result of the Energy Transitions Ministerial Meeting (ETMM), in Bali, last September 2022, which contained nine principles. The "Bali Compact" is an important part of accelerating the energy transition. The G20 Summit, the Bali Leader’s Declaration document can be reached and agreed upon by all state leaders present.